Food contamination with cadmium-A review. - PAPAVERGOU (Α. ΠΑΠΑΒΕΡΓΟΥ) A.; GEORGANTELIS (Δ. ΓΕΩΡΓΑΝΤΕΛΗΣ) D.; VARELTZIS (Κ. ΒΑΡΕΛΤΖΗΣ) K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Levels of cadmium in the environment have drastically increased over the last decades, as a result of human activity. This cadmium pollution is transferred to the human food chain resulting in elevated concentrations in some foods such as vegetables and grain crops, animal liver and kidney and especially seafood. Cadmium ingested by animals and humans, accumulates mainly in the renal cortex and may result in a variety of toxic effects, such as renal damage, bone degeneration and cancer. Taking into account the rather elevated concentrations of cadmium in offal and seafood appearing in the international literature, a continuous control of such products is suggested as necessary in order to protect consumers from any undue exposure to this heavy metal.